The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.2307/3579865
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Communication Is Involved in the Bystander Regulation of Gene Expression in Human Cells Exposed to Very Low Fluences of Alpha Particles

Abstract: We demonstrate by western analysis that the expression levels of TP53 (formerly known as p53), CDKN1A (formerly known as p21Waf1), CDC2 (formerly known as p34cdc2), CCNB1 (cyclin B1) and RAD51 are significantly modulated in confluent, density-inhibited human diploid cell populations exposed to doses where only a small fraction of the nuclei are actually traversed by an alpha-particle track. The extent of modulation of TP53 and CDKN1A is significantly reduced in the presence of the gap junction inhibitor lindan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
294
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 453 publications
(310 citation statements)
references
References 12 publications
13
294
1
2
Order By: Relevance
“…The central dogma for radiation biological effects, that only cells directly hit by radiation will suffer genetic damage, is now confronted by evidence that 'bystander' cells neighboring directly hit cells can also express biological responses/genetic damage following stress signals from adjacent irradiated cells (Nagasawa and Little, 1992;Azzam et al, 1998;Huang et al, 2007). Radiation-associated bystander responses have important implications for radioprotection, as the target for low-dose radiation damage would be larger than the directly-hit tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The central dogma for radiation biological effects, that only cells directly hit by radiation will suffer genetic damage, is now confronted by evidence that 'bystander' cells neighboring directly hit cells can also express biological responses/genetic damage following stress signals from adjacent irradiated cells (Nagasawa and Little, 1992;Azzam et al, 1998;Huang et al, 2007). Radiation-associated bystander responses have important implications for radioprotection, as the target for low-dose radiation damage would be larger than the directly-hit tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Bystander effects induced by ionizing irradiation have been studied by various approaches including transfer of conditioned medium from irradiated cells (Lyng et al, 2002;Maguire et al, 2005), low particle fluence irradiation, where only a few percent of cells are irradiated (Azzam et al, 1998), and targeted irradiation of single cells and subcellular structures (Shao et al, 2004;Shao et al, 2003bShao et al, , 2005. They have been shown to occur in both tumour and normal cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence has accumulated recently suggesting that a factor or signal can be released by irradiated cells which can affect unexposed cells in the field following high LET radiation (Nagasawa and Little, 1992;Deshpande et al, 1996;Azzam et al, 1998;Lorimore et al, 1998). Cells that are not even in the field can be affected by medium harvested from irradiated cells exposed to low doses of low LET radiation Seymour, 1997, 1998;Mothersill 1997, 2000).…”
mentioning
confidence: 99%
“…Lehnert and Goodwin (1997) reported a short-lived factor generated from α irradiated culture medium containing serum and a longer-lived factor generated from irradiated fibroblasts. Azzam et al (1998) showed that the expression levels of TP53, CDKN1A, CDC2, CCNB1 and RAD51 are significantly modulated in human fibroblast cell lines that were irradiated with very low fluences of α particles. While the name is not perhaps ideal, all these effects are collectively known as 'radiation induced bystander effects'.…”
mentioning
confidence: 99%